Influence of hydropower dams on the state of macroinvertebrates assemblages in the Virvyte river, Lithuania - Vaikasas, Saulius; Palaima, Kęstutis; Pliūraite, Virginija (Journal of Environmental Engineering and Landscape Management, 2013)
Macroinvertebrate organization along the Virvytė River was examined to relate biological response in environmental changes. Benthic macroinvertebrates and a range of environmental variables were sampled from three study sections: control, HPP dams and below HPP dams. Total macroinvertebrate taxon number (NT = 28), EPT taxon number (NT = 13) and Shannon-Wiener diversity index (H′ = 3.85) were the highest in control sites of the river and the smallest in HPP dams (17, 5, 2.75, respectively). Taxon number and total abundance of macroinvertebrates declined significantly both in HPP dams and below them in comparison with the control sites. Total macroinvertebrate abundance in the control sites (698±41 ind.m−2) was significantly higher than in HPP dams and below them (430±21 ind.m−2 and 425±22 ind.m−2, respectively). The obtained data show that the investigated sections differed in terms of composition and relative abundance of different taxa of macroinvertebrates. Compared to reference conditions (control sites), macroinvertebrate samples from the sites below the dams and in them had relatively more Chironomidae larvae, Oligochaeta and Mollusca and fewer of the more sensitive taxa Plecoptera, Ephemeroptera and Trichoptera. According to Danish Stream Fauna Index and Hilsenhoff biotic index, water quality in the Virvytė River control sites was higher in comparison with water quality in HPP dams and below-dam sites.